A Review of Intervention Studies Conducted with Individuals with Autism and Sensory Impairments. (July 2014) - Banda, Devender R.; Griffin-Shirley, Nora; Okungu, Phoebe A.; Ogot, Orpa P.; Meeks, Melanie K.
Introduction: Recently, there has been heightened interest in individuals with autism and sensory impairments, and interventions that affect this population. To date, no reviews have analyzed intervention studies, and the present study adds to intervention research literature. Methods: Based on an electronic search, eight studies were included in the review. Results: The results indicated that four of the studies focused on communication skills, while the other four targeted problem behaviors. All participants made progress in communication and showed improvements in their behaviors. Discussion: Although positive results were seen in all participants, the studies suffer from methodological limitations. Thus, future research is needed to replicate studies as well as provide maintenance and generalization data. Implications for practitioners: Some suggestions are to include preference assessments prior to the development of intervention studies to create a modified picture exchange communication system with tangible objects or symbols.